Heterogenous impact of energy security and environmental regulations on energy transition: Exploring the disparity between high-income and middle-income countries - Lin, Keliang; Ghosh, Sudeshna; Abbas, Shujaat; Shahbaz, Muhammad; Ferraz, Diogo [UNESP]; Doğan, Buhari (Elsevier, 2024)
This study investigates the impact of energy security, environmental regulation, economic complexity, globalization, and geopolitical risk on the process of energy transition. To this end Methods of Moment Quantile regression is employed on panel data of twenty-one high-income countries and nine middle-income countries from 1996 to 2018. Findings indicate that energy insecurity and environmental regulation have positive impact on energy transition in both high income and middle-income countries. However, high geopolitical risk significantly reduces the positive effects of energy insecurity on energy transition. Further, the quantile regression reveals the heterogenous impact of these factors across the energy transition distribution. In view of such findings, the policy implications suggest that the governments in high-income countries should take advantage of the favorable aspects of energy insecurity and geopolitical risk to transform their energy structure, enforce stringent environmental policies and manage the negative implications of economic complexity on energy transition. Governments in middle-income countries should try to use effectively the energy insecurity and the globalization process. There is a need to control the negative influence of geopolitical risk on energy transformation.
Keywords: Economic complexity; Energy security; Energy transition; Environmental regulation; Geopolitical risk; Globalization